52 Adherence to the ESC 2013 cardiac pacing guidelines. (28th September 2016) - Bakhet, M; Murphy, L; Nash, P
Abstract : Background: The advent of permanent pacemakers and implantable defibrillators in the mid-to-late 20 th century called for a standardised set of guidelines outlining the appropriate use of this technology. This audit proposed to identify the adherence to the 2013 ESC Practice Guidelines over a one-year period in a single tertiary referral centre. Methods: This study was performed in University Hospital Galway. All patients who underwent a new pacemaker/ICD insertion or a box change of an existing device within the one-year period of January 1 st 2015 to December 31 st 2015 were included. Information on the documented indication for the pacemaker/ICD insertion was obtained through discharge summaries, medical charts and catheterisation lab record reviews, as well as from the pacing registry G-Pace. Results: 292 patients were included (69.2% male) with an average age of 74.24 ± 14.055 years. 188 pacemaker and 42 ICD implantations were performed with 62 box changes for existing devices. 199 (68.2%) were referrals from within the centre, and 93 patients (31.8%) were transfers from another hospital. A total of 105 (36.0%) procedures were elective, and 187 (64.0%) non-elective insertions were performed as an inpatient. Of the 292 patients included in the study, 248 (84.9%) had Class I indications, 30 (10.3%) had Class IIa indications, 5 (1.7%) had Class IIb indications, 5 (1.7%) had Class III indications, and 3 (1.03%) were unknown (all of whom presented for elective box changes). The Class III indications included recurrent syncope, bifascicular block, and trifascicular block, without definite symptoms. 1(0.3%) patient had a Class II indication under the ACC/AHA guidelines, as they did not fall within the scope of the ESC guidelines. A full table of pacemaker indications can be found in table 1 . Conclusion: This audit shows a 96.9% adherence rate to the 2013 ESC Guidelines with those devices inserted for Class I/IIa/IIb indications. With the potential complications associated with cardiac devices, adherence to these guidelines is essential in minimising morbidity for the patient and maximising the use of healthcare resources. This audit demonstrates that the ESC Guidelines have been successfully integrated into practice.